Predicting the ultimate capacity of frictional jacked concrete piles installed in mixed silty sands in the Philippines - Buensuceso, Benjamin B. III (Philippine Engineering Journal, 2022)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/8900/7826